1997
DOI: 10.1055/s-2008-1035044
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Energiestoffwechsel der humanen Hornhaut in verschiedenen Kultursystemen

Abstract: The severe anaerobic situation in Optisol stored corneas leads to a lack in energy recruitment. This reduces the ability of cell function (mitosis) and the function of the monolayer (migration, elimination). Whether these changes are reversible after transplantation has to be determined in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The gaps in the endothelial cell layer were limited to the size of a single cell, and there was no significant decrease in cell density, which remained well above 2000 cell/mm 2 . These findings were similar to those of porcine corneoscleral tissue that had been stored for 13 days 33 and human corneoscleral tissue stored for 14-15 days. 1,17 Van Horn et al 7 has already reported that the endothelial cell layers of feline and human corneosceral tissue react similarly during storage, and they proposed the cat as an experimental model in human studies of the cornea.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The gaps in the endothelial cell layer were limited to the size of a single cell, and there was no significant decrease in cell density, which remained well above 2000 cell/mm 2 . These findings were similar to those of porcine corneoscleral tissue that had been stored for 13 days 33 and human corneoscleral tissue stored for 14-15 days. 1,17 Van Horn et al 7 has already reported that the endothelial cell layers of feline and human corneosceral tissue react similarly during storage, and they proposed the cat as an experimental model in human studies of the cornea.…”
Section: Discussionsupporting
confidence: 83%
“…29 Similarly, Redbrake et al . 33 did not find any significant difference in cell densities of control tissue and human corneal tissue that had been stored in Optisol ® GS for 13 days. However, they cautioned that it was not possible to accurately assess the loss of endothelial cells during storage, because dead or damaged cells cannot be eliminated from the endothelial layer at 4 °C.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations